Mutational analysis of the bacterial signal-transducing protein kinase/phosphatase nitrogen regulator II (NRII or NtrB). - Atkinson, M R (1993)
The signal-transducing kinase/phosphatase nitrogen regulator II (NRII or NtrB) is required for the efficient positive and negative regulation of glnA, encoding glutamine synthetase, and the Ntr regulon in response to the availability of ammonia. Alteration of highly conserved residues within the kinase/phosphatase domain of NRII revealed that the positive and negative regulatory functions of NRII could be genetically separated and that negative regulation by NRII did not require the highly conserved His-139, Glu-140, Asn-248, Asp-287, Gly-289, Gly-291, Gly-313, or Gly-315 residue. These mutations affected the positive regulatory function of NRII to various extents. Certain substitutions at codons 139 and 140 resulted in mutant NRII proteins that were transdominant negative regulators of glnA and the Ntr regulon even in the absence of nitrogen limitation. In addition, we examined three small deletions near the 3' end of the gene encoding NRII; these resulted in altered proteins that retained the negative regulatory function but were defective to various extents in the positive regulatory function. A truncated NRII protein missing the C-terminal 59 codons because of a nonsense mutation at codon 291 lacked entirely the positive regulatory function but was a negative regulator of glnA even in the absence of nitrogen limitation. Thus, we have identified both point and deletion mutations that convert NRII into a negative regulator of glnA and the Ntr regulon irrespective of the nitrogen status of the cell.